2011
DOI: 10.1186/1471-2407-11-401
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the apparent breast cancer epidemic in France: screening and incidence trends in birth cohorts

Abstract: BackgroundOfficial descriptive data from France showed a strong increase in breast-cancer incidence between 1980 to 2005 without a corresponding change in breast-cancer mortality. This study quantifies the part of incidence increase due to secular changes in risk factor exposure and in overdiagnosis due to organised or opportunistic screening. Overdiagnosis was defined as non progressive tumours diagnosed as cancer at histology or progressive cancer that would remain asymptomatic until time of death for anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Warner and colleagues found a higher incidence of breast cancer in the first 3 years after the introduction of MRI screening in BRCA1/2 mutation carriers and an overall higher incidence of DCIS (26). This effect has also been shown in the general population after introduction of the population-based breast cancer screening with mammography (27,28). This explanation is weakened by the fact that this effect was not seen in BRCA2 mutation carriers.…”
Section: Discussionmentioning
confidence: 95%
“…Warner and colleagues found a higher incidence of breast cancer in the first 3 years after the introduction of MRI screening in BRCA1/2 mutation carriers and an overall higher incidence of DCIS (26). This effect has also been shown in the general population after introduction of the population-based breast cancer screening with mammography (27,28). This explanation is weakened by the fact that this effect was not seen in BRCA2 mutation carriers.…”
Section: Discussionmentioning
confidence: 95%
“…A case‐control study determined that the total average costs of breast cancer was 107,456€/patient, being 89% productivity loss costs and 11% health care costs [4]. Different studies have investigated the incidence and prevalence rates of breast cancer; however, it has been recently reported that incidence rates of breast cancer have been overestimated in the last decade [5,6]. In fact, a recent report has shown that breast cancer mortality has decreased in Europe over the last 25–30 years [7].…”
Section: Introductionmentioning
confidence: 99%
“…This is a well-known phenomenon, which has been demonstrated in studies displaying age–cohort graphics (Brown et al , 2009; Martinez-Alonso et al , 2010; Junod et al , 2011) or age–period graphics (Svendsen et al , 2006; Otten et al , 2008; Pollán et al , 2010). …”
Section: Discussionmentioning
confidence: 82%